Development of a high-speed, phase-sensitive laser probe system for RF surface/bulk acoustic wave devices with an autofocus function for long-time continuous operation. (1st July 2022) - Kawai, Kazuki; Takahashi, Hikaru; Omori, Tatsuya; Hashimoto, Ken-ya
Abstract: This paper describes the implementation of an autofocus function for a laser beam in a high-speed, phase-sensitive laser probe system for RF surface/bulk acoustic wave devices. This implementation can compensate for defocus caused during continuous measurements that take dozens of hours. After a brief explanation of the system used in this work, a detailed discussion is given on the employed evaluation function indicating focus status, which is a key factor determining autofocus reliability. It is shown that the sum of the energies of Laplacians is suitable as an evaluation function, which can be calculated by an image of the probing laser spot captured by a built-in CCD camera. Then, the implementation of the autofocus function in the current system is detailed. It is confirmed that this function can adjust the focus within almost ± 20 μ m defocus conditions. Finally, it is confirmed how the implemented autofocus function works effectively to keep just-in-focus under disturbance.